Transabdominal Ultrasound-Guided Transjugular Intrahepatic Portosystemic Shunt Placement between Left Hepatic Vein and Left Portal Vein: A Technical Note - Rajesh Sasidharan; Shubham Suryavanshi; Akhil Baby (Journal of Clinical Interventional Radiology ISVIR, 2025)
The conventional approach for transjugular intrahepatic portosystemic shunt (TIPS) involves creating a communication between the right hepatic vein and the right branch of the portal vein. However, some studies suggest that TIPS placement between the left hepatic vein and the left portal vein branch may reduce the risk of hepatic encephalopathy. This left-to-left TIPS technique can also be beneficial for patients with an attenuated or thrombosed right portal vein, an atrophied right lobe, or those who have undergone a right hepatectomy or liver transplant with a left lobe graft. Here, we present our technique for performing left-to-left TIPS using transabdominal ultrasound guidance.